2019
DOI: 10.1007/s10854-019-02031-3
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, optical and dielectric properties of cerium oxide thin films prepared by pulsed laser deposition

Abstract: Cerium oxide (CeO2) thin films were deposited on Pt (111)/Ti/SiO2/Si(100) substrates using pulsed laser deposition (PLD) method at different temperatures such as, 300 K, 573 K and 873 K with 3×10-2 mbar oxygen partial pressure. The prepared films were systematically investigated using X-ray diffraction (XRD), atomic force microscopy (AFM), photoluminescence (PL) and electrical measurement system. XRD analysis clearly shows improved crystallinity of CeO2 films prepared at 573 and 873 K substrate temperatures. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…To confirm the modulation of the electric field in the CeO 2 layer and SiO 2 layer, the fabricated device with exact dimensions was numerically simulated using a commercial grade TCAD simulation tool (ANSYS Lumerical Device R2022b) . Note that the CeO 2 layer is modeled as a dielectric layer with a relative permittivity of 17 at 300 K . The simulated electrostatics shown in Figure (e)–(j) indicate the influence of two opposing electric fields between the three terminals, confirming the proposed mechanism, as discussed earlier.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…To confirm the modulation of the electric field in the CeO 2 layer and SiO 2 layer, the fabricated device with exact dimensions was numerically simulated using a commercial grade TCAD simulation tool (ANSYS Lumerical Device R2022b) . Note that the CeO 2 layer is modeled as a dielectric layer with a relative permittivity of 17 at 300 K . The simulated electrostatics shown in Figure (e)–(j) indicate the influence of two opposing electric fields between the three terminals, confirming the proposed mechanism, as discussed earlier.…”
Section: Resultssupporting
confidence: 81%
“…As depicted in Figure 1(b), the strong electric field in the CeO 2 -based switching layer will aid in the formation of the CBs. However, as CeO 2 is a high-k dielectric material 43 and the metal electrodes are very thin (∼40 nm), the electric field will partially penetrate the metal electrodes. 44 Although in the 2T configuration this effect will have minimal impact on the I−V characteristics, it will have an important role in converting the bipolar characteristics of the memristor into unipolar characteristics in the 3T configuration.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Additionally, the oxygen vacancies in dielectric thin film act as mobile carriers for current conduction. A larger concentration of oxygen vacancies results in a high leakage current which indicates that at higher substrate temperatures the oxygen vacancies reduce in the thin film [58]. This also confirms the reduction of oxide charge density with increase in substrate temperature as obtained from the C-V measurement.…”
Section: Effect Of Substrate Temperaturesupporting
confidence: 76%
“…[17][18][19][20][21] Besides, the use of high k CeO 2 would prevent premature breakdown of the devices as a lower electric field is induced on the passivation layer relative to the Si substrate. 22 Another versatility of CeO 2 phase in transforming from oxidizing (Ce 4+ ) to reducing (Ce 3+ ) state has attracted its employment in catalytic applications but this feature was deemed to result in detrimental effect towards the passivating properties of CeO 2 layer 23 caused by the formation of low k SiO 2 interfacial layer, of which its presence would ultimately reduce the overall k value of the device. 24 Although eradicating the formation of interfacial layer would be very challenging, previous studies reported about the enhancement in breakdown voltage and leakage current due to the interfacial layer formation coupled with an acceptable interface quality between CeO 2 passivation layer and Si substrate.…”
Section: Introductionmentioning
confidence: 99%